2016
DOI: 10.1007/s00122-016-2767-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of QTL for the sizes of eight consecutive leaves below the tassel in maize (Zea mays L.)

Abstract: A set of RIL population was used to detect QTL associated with the sizes of eight consecutive leaves, across different environments, and ten QTL clusters were identified as main QTLs. One of the important parameters of the maize leaf architecture that affects light penetration into the canopy, leaf size, has long attracted breeders' attention for optimizing the plant type of maize and for maximizing the grain yield (GY). In this study, we used 253 RIL lines derived from a cross between B73 and SICAU1212 to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 97 publications
2
27
1
Order By: Relevance
“…). This contrasts to a study in wheat (Yang et al ) working with biparental population found that leaf width was less variable compared to leaf length. In our diversity panel, we found an even larger importance of leaf width on individual leaf area compared to that of leaf length (85% versus 15% of explained variance).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…). This contrasts to a study in wheat (Yang et al ) working with biparental population found that leaf width was less variable compared to leaf length. In our diversity panel, we found an even larger importance of leaf width on individual leaf area compared to that of leaf length (85% versus 15% of explained variance).…”
Section: Discussioncontrasting
confidence: 99%
“…Within the few studies considering leaf width, most of them have shown that a larger part of variance of individual leaf area in biparental population was explained by leaf width compared to that by leaf length (Wei et al2016 ;Yang et al 2016a). This contrasts to a study in wheat (Yang et al 2016b) working with biparental population found that leaf width was less variable compared to leaf length. In our diversity panel, we found an even larger importance of leaf width on individual leaf area compared to that of leaf length (85% versus 15% of explained variance).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Epistasis, or the interaction of a pair of loci may play an important role in the genetic of complex quantitative traits [18,52]. If epistasis is ignored, many individual loci could not be detected, which will weaken the detection power of QTL [53].…”
Section: Genetic Basement Of Epistasis Qtl and Interactions With Envimentioning
confidence: 99%